Modernisasi Pendidikan: Analisis Pemanfaatan Sumber Daya Manusia Dan Teknologi Untuk Peningkatan Kualitas Pembelajaran Di Ma’had Aly - Himami, Nely; Yunus, Moch.; Lailia Maghfiroh, Ummi (Kartika: Jurnal Studi Keislaman, 2025)
The modernization of education in traditional Islamic institutions is inevitable amidst the progress of time and the demands for high-quality human resources. This study aims to analyze the utilization of human resources and technology in improving the quality of learning at Ma’had Aly Pesantren Zainul Hasan Genggong Probolinggo. Employing a descriptive qualitative approach, data were collected through observation, in-depth interviews, and documentation. The results indicate that human resources are optimized through lecturer competence development, regular training, and competency-based recruitment. Meanwhile, technology utilization is reflected in the use of digital learning media, academic information systems, and online platforms. The integration of qualified human resources and adaptive technology significantly impacts the effectiveness of learning processes and graduate quality. These findings highlight the importance of synergy between human and technological resources in addressing the challenges of educational modernization in pesantren environments.